Pay and Incentive Inequality: A Systematic Review of Their Effects on Work Motivation - Hasyim, Hasyim; Bakri, Muhammad (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study systematically examines the impact of pay and incentive inequality on work motivation, focusing on the interplay between monetary and non-monetary incentives, organizational factors, and demographic contexts. By addressing critical gaps in the literature, the research seeks to provide actionable insights into designing equitable and effective compensation systems. A systematic literature review (SLR) synthesized findings from diverse studies across various sectors and demographics. The analysis integrated theoretical frameworks such as Equity Theory and Self-Determination Theory (SDT) to explore how compensation systems influence employee motivation and organizational outcomes. The findings reveal that pay and incentive inequality significantly affect employee motivation and well-being, with disparities in compensation leading to perceptions of injustice, reduced engagement, and higher turnover. Monetary incentives are effective for short-term productivity but insufficient for sustaining intrinsic motivation without complementary non-monetary rewards. Organizational culture, transparency, and demographic factors, such as age, gender, and geographic location, were found to mediate the impact of compensation disparities. Additionally, the study underscores the need for context-specific compensation strategies to address systemic inequities and enhance motivation. The study highlights the importance of transparent and inclusive compensation policies for fostering equity and long-term organizational sustainability. Practical recommendations include combining monetary and non-monetary incentives, engaging employees in policy design, and tailoring strategies to demographic and geographic contexts. These insights contribute to developing equitable workplaces and inform future research directions.